Digital Natives or Digitally Naive? E-professionalism and Ethical Dilemmas Among Newly Graduated Teachers and Social Workers in Ireland - KIRWAN, GLORIA; MCGUCKIN, CONOR (My University, 2014)
n a study which examined how newly qualified teachers and social workers conceptualize and incorporate asynchronous technologies in their professional and private spheres, variation in active participation on social media among the participants reflected a spectrum of opinions regarding the implications of online interaction for new professionals. The extent to which online interaction can overlap with ethical expectations attaching to professional roles is an emerging topic in the research literature. This study focused on the activities and experiences of newly qualified professionals. In this article, ethical issues are examined in three categories, namely formation, maintenance, and ending of online relationships.
PUBLISHED
Keywords: Education; asynchronous technology; e\-professionalism; ethics; social media; social work; teaching; Identities in Transformation